RELATIONSHIP OF KNOWLEDGE LEVEL ABOUT ALCOHOLIC DRINKS AND CONSUMPTION BEHAVIOR OF ALCOHOLIC DRINKS IN STUDENT OF SENIOR HIGH SCHOOL 1 KUPANG - Juniar Sanjas Fajareni (Universitas Nusa Cendana, 2025)
The World Health Organization (WHO) states that alcohol use causes 3.3 million deaths each year and accounts for 60 types of diseases due to alcohol abuse. EastNusa Tenggara occupies the first province with the highest prevalence of drinking alcohol and is the second largest province with the population who consume alcohol. Per capita alcohol consumption is mostly consumed by adolescents aged 15-19 years. Data from BPS 2012 showsthat 83.1% of Indonesian adolescents have ever consumedalcohol. The consumption of alcoholic beverages can causeserious health problems.